Nutritional Status of Crossocheilus latius latius (Hamilton, 1822) and Garra lamta (Hamilton, 1822) from Alaknanda River of Central Himalaya. Issue 4 (20th April 2020) - Sharma, Sharali; Singh, Deepak
ABSTRACT: Crossocheilus latius latius and Garra lamta are commonly found in the Alaknanda River and its tributaries, and are consumed by local inhabitants. The present investigation was aimed to determine the chemical composition and nutritional status of these fishes, so that priority can be given to their consumption. The fish samples were collected from the major Himalayan river, Alaknanda, and its tributary with the help of local fishermen. Total soluble protein and carbohydrate contents were found to be highest during the summer season, with 24.03% and 2.34%, respectively, in Crossocheilus latius latius, and 24.28% and 2.21%, respectively, in Garra lamta . Total moisture content and lipid content were found to be highest during the monsoon season in both C. latius latius (75.50% and 2.62%, respectively) and G. lamta (75.06% and 2.44%, respectively). Calcium and iron were found to be the dominant mineral elements in fish tissue. No significant difference was found between C. latius latius and G. lamta with respect to chemical constituents and trace elements. However, macroelements showed a significant difference, indicating C. latius latius to be rich in Ca and K, while G. lamta was a good source of Na content. Trace elements were recorded below the highest permissible limit of Food and Agriculture Organization; hence, the fish are recommended safe and healthy for human consumption.